Normalization Factors of Jordan's Diplomatic Relationship with Qatar: Dynamics Analysis of Area Security and National Identity - Abdullah Hamidi (International Journal of Science and Society, 2020)
Jordan as a country that is flanked by several countries in conflict and does not have a wealth of natural resources, making alliances very important for the survival of the country. In meeting these needs, Jordan often allies with hegemonic actors for protective status as well as financial assistance. So in the scope of the Middle East, Jordan chose an alliance with the country of Saudi Arabia and its coalition in the Gulf region in the Gulf Cooperation Council. This alliance was continued until the 2017 Qatar diplomatic crisis, Jordan was forced to cut ties with Qatar so that the alliance with the Saudi kingdom would not be damaged. However, in 2019, Jordan normalized diplomatic relations with Qatar after their two-year stretch. This decision also came even though Saudi Arabia and its coalition had not normalized with Qatar itself, and could potentially jeopardize Jordan's existence if it did so because it was against the Saudi coalition. So the researcher tries to analyze this phenomenon using regional security theory and the level of national identity analysis. Researchers later found that the motive behind the decision was Qatar's support for the protective status of Jordan's Jerusalem.